Two Edges of Sword of Strategy-Based Instruction (SBI) and Implicit Task-Based Instruction (TBI) on EFL Oral Performance - Dony Marzuki (Universitas Hamzanwadi, 2022)
This pilot study aimed to investigate the effects of two classroom instructions on the complexity, accuracy, and fluency of EFL learners’ speaking. The first one involved implicit task-based instruction with meaning-focused pedagogic tasks. The second instruction reduced learners’ practice time but complemented it with explicit strategy-based instruction (SBI) to raise their metacognitive awareness in planning, monitoring, and evaluating their speech. Participants in the explicit instruction group learned to practice three specific strategies, while the first group had only more practice opportunities. The study involved 16 English students from a third-tier university in Indonesia. Audio recordings of each participant’s oral presentations during the pre-test and the post-test were transcribed and coded for non-parametric analysis. The findings revealed that both instructions had a comparable impact on EFL learners' oral performance by improving complexity but not accuracy and fluency. There was also a possible trade-off effect found in participants’ performance. The study findings could provide a basis for EFL teachers to use either explicit strategy instruction or implicit instruction for their speaking class.